Pengaruh Model Pembelajaran Role Playing Terhadap Hasil Belajar Siswa pada Mata Pelajaran Al-Qur’an Hadist Kelas XI di MA Al-Ihsan Kalikejambon Tembelang Jombang - Permatasari, Deni; Wahyudi, Wahyudi; Husna, Asiyah Lu'lu'ul (Universitas KH. A. Wahab Hasbullah, 2022)
The purpose of this study is to find out: 1. The use of role playing learning models in the subjects of the Koran, 2. Student learning outcomes in the subjects of the Koran, 3. Significant effects between the role playing learning models on student learning outcomes in al- the quran. This research is a quantitative study with a quasi-experimental approach. The population in this study were students of class XI MA Al-Ihsan totaling 49 students. The sample was divided into 2 classes, namely class XI IIS which amounted to 29 students as the experimental class and class XI MIPA totaling 18 students as the control class. In the experimental class, a role playing learning model is applied, while in the control class a varied lecture method is applied. From the data analysis, it was found that the experimental class which was taught using the role playing learning model obtained a pretest score of 70.1724 and a posttest score of 88.6207 with the difference in the average increase in learning outcomes 18. 4483. In the control class taught by conventional learning (without using role playing learning) obtained scores pretest 58.8889and posttest score 82.5000 with the difference in the average increase in learning outcomes 23.6111.